Peran Komunikasi Dai Dalam Membangun Kesadaran Beragama Masyarakat Muslim di Desa Terang Bulan Kecamatan Aek Natas Kabupaten Labuhanbatu Utara - Ritonga, Joni Romaito; Muktaruddin, Muktaruddin; Salamuddin, Salamuddin (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This research aims to determine the role of Dai communication in building religious awareness in Muslim communities in Terang Bulan Village, Aek Natas District, North Labuhanbatu Regency. The Role of Dai Communication in Building Religious Awareness of Muslim Communities in Terang Bulan Village, Aek Natas District, North Labuhanbatu Regency. This research will be carried out from June 2023 to July 2023 in Terang Bulan Village, Aek Natas District, North Labuhanbatu Regency. It consists of 4 informants selected according to predetermined criteria. The data sources used use primary and secondary data sources. Data collection was carried out by direct observation, interviews and documentation. Data analysis consists of four processes, namely data reduction, data display, data conclusion/verification. Then check the validation of the data in the research carried out. Triangulation in credibility testing is defined as checking data from various sources in various ways, and at various times. The results of the research are that the communication role of preachers in the village of Terang Bulan, Aek Natas sub-district, North Labuhanbatu district makes a lot of contributions to the community in terms of worship, religious harmony because every problem or thing that triggers heterogeneous religious awareness in Bright Bulan is immediately suppressed and discussed by the preachers. , a policy and decision is taken based on the common good and benefit to continue to live side by side well. The preachers in the light of the moon in Labuhanbatu are still role models for the Muslim community there. Every time there is a problem, they still ask questions and listen to what the preachers have to say. The technique used by the preacher is to provide understanding through policy actions in each problem and complete studies to continue to convey the truth of Islamic teachings as a medieval community and learn religious knowledge and then practice its teachings. Keywords: the role of Dai communication, Awareness, Religion